Nurses' Awareness of Patient Privacy and Confidentiality in Benghazi Medical Centre (BMC): A Cross-sectional Study - Omar, Fatma Abdalla Atitalla; Eltarhuni, Ainas Salem; Elamrony, Randa Mahmoud Gadalla; Kutran, Huda (Libyan Journal of Dentistry, 2023)
Background:- Respect for the privacy of patients and the confidentiality of their information, personal data is a fundamental principle of patient rights. All healthcare providers, especially physicians and nurses play a crucial role as guardians of patient safety and rights therefore this study aimed to assess the knowledge and awareness of patients’ rights among nurses at the Benghazi Medical Center. Methods: A cross-sectional descriptive study was conducted with 184 nurses at the gynecology and obstetrics department of the Benghazi Medical Center, using a self-administrated questionnaire. The questionnaire consisted of three parts: personal characteristics, and the knowledge towards privacy part (21 statements), and confidentiality (11 statements). Data analysis was carried out using SPSS version 23. Descriptive statistics (frequencies, percentages, means, and standard deviations) were used to describe the knowledge of privacy and confidentiality among nurses. A relation test was used to measure the association between privacy and confidentiality with personal data. Also, statistical significance was set at a P- value of <0.05. Results: 67.9% of the nurses reported that they had experienced patient rights. The knowledge about privacy among nurses in the target hospital was high, and the most common knowledge was: during the examination, treatment, and care, all healthcare professionals should be careful about the protection of patient privacy (91.8%) and nursing care to protect privacy in the work environment (91.3%). Concerning confidentality, nurses had a high level of knowledge in general, and the highest level of knowledge was in the statement ‘patients must get all kind of health service in an environment that is suitable for confidentiality’. The result found there was no association between personal characteristics and privacy and confidentiality. Conclusion:- It was concluded that nurses commonly encounter patient rights issues in their workplace. However, the majority of the nurses who participated in the study had a very good level of knowledge about privacy and confidentiality. Age, educational level or length of working experience was insignificantly associated with the level of knowledge of privacy and confidentiality.